Diseño de un sistema de gestión del área de talento humano para el desarrollo de la distribuidora de Joyas Kilates - Aguirre Ramírez, Ashley del Rocío (2021)
This research is carried out to design the proposal for a management system for the human talent area for the development of the Kilates jewelry distributor, given that they do not have proper administrative management based on the human resources area, which prevents them from managing in a better way their corporate image. The exploration takes place in the Palestine canton where the intermediary is located. To cover the context, an interview is conducted with the manager who owns Kilates jewelry, in which the present reality is determined, and data on the organizational culture is compiled, demonstrating its weakness due to the lack of an area dedicated to managing staff goals and the strengths that will be obtained with the correct direction of this area through training, feedback and support to collaborators.............